Intra-arterial alteplase for acute ischaemic stroke after mechanical thrombectomy (PEARL): rationale and design of a multicentre, prospective, open-label, blinded-endpoint, randomised controlled trial - Jie Li; Yajie Liu; Min Zhang; Haoyang Sun; Yingying Zhu; XinGuang Yang; Dong Pan; Yamei Tang; Hongbiao Hou; Xiongjun He; Yongteng Xu; Huiyuan Peng; et al. (BMJ Open)
Introduction Successful reperfusion does not always lead to good neurological outcomes and impaired microcirculation can be one of the underlying causes. Intra-arterial alteplase after mechanical thrombectomy (MT) may improve microcirculation contributing to neurological recovery, but prospective randomised studies are still needed to validate its efficacy and safety. We aim to assess the efficacy and safety of intra-arterial alteplase after MT for acute ischaemic stroke (AIS) with large-vessel occlusion (LVO).Methods and analysis The Intra-arterial Alteplase for Acute Ischaemic Stroke After Mechanical Thrombectomy (PEARL) study is a multicentre, prospective, open-label, blinded-endpoint, randomised controlled trial. We consecutively screen AIS patients with anterior circulation LVO and National Institute of Health Stroke Scale of 6–25, who reach stable expanded Thrombolysis in Cerebral Infarction scores of 2b50-3 on angiography after MT. Eligible participants are 1:1 randomly assigned to the experimental group and the control group. Participants in the experimental group will receive intra-arterial alteplase (0.225 mg/kg and a maximum dose of 20 mg) after MT and standard medical treatment, while those in the control group will receive standard medical treatment alone after the procedure. The primary outcome is the proportion of patients with a 90-day modified Rankin scale of 0–1. A total of 324 participants are required to test the superiority hypothesis with 80% power at a two-tailed significance level of 0.05.Ethics and dissemination This study has been approved by the Ethics Committee of Sun Yat-sen Memorial Hospital, Sun Yat-sen University (SYSKY-2023-390-02) and will be conducted following the Declaration of Helsinki. Ethical approvals have been obtained separately for all centres participating in the study. Study results will be published in peer-reviewed academic journals.Trial registration number NCT05856851.